The Race Card: from Gaming Technologies to Model Minorities - Fickle, Tara (New York University Press, 2020)
This book uncovers popular games' key role in the cultural construction of modern racial fictions. It argues that gaming provides the lens, language, and logic - in short, the authority - behind racial boundary making, reinforcing and at times subverting beliefs about where people racially and spatially belong. It focuses specifically on the experience of Asian Americans and the longer history of ludo-Orientalism, wherein play, the creation of games, and the use of game theory shape how East-West relations are imagined and reinforce notions of foreignness and perceptions of racial difference.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé